Afferent Input Induced by Rhythmic Limb Movement Modulates Spinal Neuronal Circuits in an Innovative Robotic In Vitro Preparation. (1st December 2018) - Dingu, Nejada; Deumens, Ronald; Taccola, Giuliano
Highlights: BIKE induces passive pedaling while allowing for electrophysiological recordings in leg-attached spinal cords in vitro . BIKE elicits rhythmic afferent volleys from DRs that affect locomotor and dorsal horn networks, with a distinct timing. Short sessions of BIKE facilitate locomotor circuits, while a long exercise potentiates dorsal horn networks. Long application of BIKE increases the frequency of both excitatory and inhibitory spontaneous input to motoneurons. Abstract: Locomotor patterns are mainly modulated by afferent feedback, but its actual contribution to spinal network activity during continuous passive limb training is still unexplored. To unveil this issue, we devised a robotic in vitro setup (Bipedal Induced Kinetic Exercise, BIKE) to induce passive pedaling, while simultaneously recording low-noise ventral and dorsal root (VR and DR) potentials in isolated neonatal rat spinal cords with hindlimbs attached. As a result, BIKE evoked rhythmic afferent volleys from DRs, reminiscent of pedaling speed. During BIKE, spontaneous VR activity remained unchanged, while a DR rhythmic component paired the pedaling pace. Moreover, BIKE onset rarely elicited brief episodes of fictive locomotion (FL) and, when trains of electrical pulses were simultaneously applied to a DR, it increased the amplitude, but not the number, of FL cycles. When BIKE was switched off after a 30-min training, the number of electrically induced FL oscillations was transitorily facilitated, without affecting VR reflexes or DR potentials. However, 90 min of BIKE no longer facilitated FL, but strongly depressed area of VR reflexes and stably increased antidromic DR discharges. Patch clamp recordings from single motoneurons after 90-min sessions indicated an increased frequency of both fast- and slow-decaying synaptic input to motoneurons. In conclusion, hindlimb rhythmic and alternated pedaling for different durations affects distinct dorsal and ventral spinal networks by modulating excitatory and inhibitory input to motoneurons. These results suggest defining new parameters for effective neurorehabilitation that better exploits spinal circuit activity.